Pengaruh Brand Image, Brand Ambassador, Word Of Mouth dan Testimony In Social Media terhadap Keputusan Pembelian Hijab Sulthanah di Kota Tegal - Agnes Dwita Susilawati; Ahmad Hanfan; Fetalia Haryanti Anugrah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2021)
This study aims to determine the effect of Brand Image, Brand Ambassador, Word of Mouth and Testimony in Social Media on Purchasing Decisions (case study on Hijab Sulthanah in Tegal City) either partially or simultaneously. This type of associative research with a quantitative approach. The sample selection used incidental sampling, totaling 100 respondents. The data analysis technique used is Multiple Linear Regression Analysis and Significance Test (classical assumption test, t test, F test, and determination coefficient test). The results of this study indicate that simultaneously the influence of Brand Image, Brand Ambassador, Word Of Mouth and Testimony in Social Media on Purchasing Decisions (case study on Hijab Sulthanah in Tegal City). Meanwhile, brand image partially affects purchasing decisions, brand ambassadors have no effect on purchasing decisions, word of mouth affects purchase decisions, and testimony in social media has no effect on purchasing decisions.